Teacher Efforts in Improving Students' Learning Motivation in IPAS Learning at SDN 26 Dompu - Ilham Ilham; Titi Pujiarti; Hidayatul Nisa (MASALIQ, 2025)
Learning motivation is a critical internal factor influencing the success of the teaching and learning process. This study investigates the role of teachers in enhancing students' learning motivation in Natural and Social Sciences (IPAS) among Grade IV students at SDN 26 Dompu. A qualitative research design was employed, with data collected through observation, interviews, and documentation. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that teachers contribute to increasing student motivation by encouraging active participation, fostering enthusiasm, offering recognition, and applying varied instructional methods. Specific strategies implemented by teachers include selecting appropriate teaching methods, utilizing educational media, conducting regular learning evaluations, creating an engaging classroom environment, and promoting both healthy competition and cooperation among students. These results underscore the essential role of teachers in fostering student motivation and engagement in IPAS learning at the elementary level.